Relevance feedback for Malay Hadith search engine using support vector machine / Hajjar Izzati Mohd Ghazali - Mohd Ghazali, Hajjar Izzati (2011)
Finding useful and relevance information is frequently a tiresome and difficult task. Therefore, Relevance Feedback is needed as it aims for more efficient result and more satisfaction from the users. Relevance feedback helps to improve the retrieval process by ranking the documents. By employing a relevance feedback technique in Mutiara Hadith Search Engine, it can facilitate the users to find related hadith based on their query(s). Furthermore, only related hadith will be displayed, which the users have chosen. This project adopts Support Vector Machine technique in Malay Hadith Search Engine and the effectiveness of the technique is evaluated using recall, precision and effectiveness. This project shows an increasing effectiveness when the technique is adopted.